The thief's daughter - Wheeler, Jeff, 1971- (Wheeler, Jeff, 1971- Kingfountain series., 2016)
"Owen Kiskaddon first came to the court of the formidable King Severn as a prisoner, winning favor with the stormy monarch by masquerading as a boy truly blessed by the Fountain. Nine years hence, the once-fearful Owen has grown into a confident young man, mentored in battle and politics by Duke Horwath and deeply in love with his childhood friend, the duke's granddaughter. But the blissful future Owen and Elysabeth Mortimer anticipate seems doomed by the king's machinations" -- back cover.